Anti-Inflammatory and Antimicrobial Effects of Estradiol in Bovine Mammary Epithelial Cells during Staphylococcus aureus Internalization - Ivan Medina-Estrada; Joel E. López-Meza; Alejandra Ochoa-Zarzosa (Hindawi Limited, 2016)
17β-Estradiol (E2), the predominant sexual hormone in females, is associated with the modulation of the innate immune response (IIR), and changes in its levels at parturition are related to intramammary infections, such as mastitis. In bovine mammary epithelial cells (bMECs), E2 regulates differentiation and proliferation, but its immunomodulatory functions have not been explored. Staphylococcus aureus is the predominant pathogen causing mastitis, which can persist intracellularly in bMECs. The aim of this work was to analyze whether E2 modulates the IIR of bMECs during S. aureus internalization. bMECs treated with E2 (50 pg/mL, 24 h) reduced bacteria internalization (~50%). The host receptors α5β1 and TLR2 do not participate in this reduction. However, E2 activates ERα and modulates the IIR reducing the S. aureus induced-mRNA expression of TNF-α (~50%) and IL-1β (90%). E2 also decreased the secretion of these cytokines as well as IL-6 production; however, in infected bMECs, E2 induced the secretion of IL-1β. Furthermore, E2 upregulates the expression of the antimicrobial peptides DEFB1, BNBD5, and psoriasin S100A7 (~5-, 3-, and 6-fold, resp.). In addition, E2 induced the production of antimicrobial compounds in bMEC culture medium, which, together with the modulation of the IIR, could be related to the reduction of S. aureus internalization.